INTEGRATING QUIZLET FOR IMPROVING STUDENTS’ UNDERSTANDING OF THE SCIENCE SUBJECT (Practitioner Research, 2019)
Nowadays, educational institutions integrate the use of assessment tool due to its efficiency in engaging students during lesson. However, many teachers are still hesitated in integrating technology in classroom for many reasons such as lack of confidence in their IT skills, no exposure to the applications which are available online, time constraint and difficulties to change their current teaching method. Students however show their interests when exposed to new applications and they are keen to learn in an interactive environment which later could lead to better performance in the examination. To implement this, the teachers should keep up with students’ preferences and they should understand that an assessment tool should be incorporated in class not just because it is fun, but also because of its ability to help teachers in improving students’ learning outcomes. The purpose of this study was to determine the effect of Quizlet on students’ achievement on Science subject and also to determine students’ perception towards the use of Quizlet. A total of 77 form 1 students from four classes have participated in this study where their examination results of before and after using Quizlet in Science subject were taken. The result showed that there is a significant improvement in their Science subject achievement when using Quizlet. The survey result shows that the students’ perception towards the use of Quizlet are positive.